2022
DOI: 10.1021/acs.jpcc.2c02674
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the Performance of Artificially Intelligent Nanopores Developed by Integrating Solid-State Nanopores with Machine Learning Methods

Abstract: Solid-state nanopores with a through-hole diameter of less than a few hundred nanometers can detect single nanoparticles owing to the ionic current flowing through the nanopore. Improvements in our understanding of the electrical properties of nanopores and the flow dynamics of a single nanoparticle passing through a nanopore have facilitated the use of machine learning methods for single nanoparticle detection. However, the sensing performance of solid-state nanopores integrated with machine learning methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Hu et al demonstrated the use of a machine learning algorithm to obtain automated classification of metabolites using a nanopore platform . Taniguchi et al reported the identification of several polystyrene nanoparticles by combining solid-state nanopore sensing with a machine learning algorithm . The same group has demonstrated that such approach can also be employed for accurate detection of different types of viruses .…”
Section: High-throughput Nanoporesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al demonstrated the use of a machine learning algorithm to obtain automated classification of metabolites using a nanopore platform . Taniguchi et al reported the identification of several polystyrene nanoparticles by combining solid-state nanopore sensing with a machine learning algorithm . The same group has demonstrated that such approach can also be employed for accurate detection of different types of viruses .…”
Section: High-throughput Nanoporesmentioning
confidence: 99%
“… 66 Taniguchi et al reported the identification of several polystyrene nanoparticles by combining solid-state nanopore sensing with a machine learning algorithm. 67 The same group has demonstrated that such approach can also be employed for accurate detection of different types of viruses. 68 A further example of a machine learning approach for discriminating analytes in mixtures is the use of the learning time-series shapelets, as exemplified by Wei et al 69 Here, the maximum discriminative features corresponding to each analyte that form a short segment of time-series data are extracted as shapelet signals and use the shapelet-transformed representation in order to classify the analytes investigated.…”
Section: High-throughput Nanoporesmentioning
confidence: 99%
“…68 Taniguchi et al reported the identification of several polystyrene nanoparticles by combining solid-state nanopore sensing with a machine learning algorithm. 69 The same group has demonstrated that such an approach can also be employed for accurate detection of different types of viruses. 70 A further example of a machine learning approach for discriminating analytes in mixtures is the use of the learning time-series shapelets, as exemplified by Wei et al.…”
Section: Machine-learning Assisted Nanopore Readoutmentioning
confidence: 99%
“…Note that these ML models are transferable, are easy to access, and can be assembled with a nanopore sequencing device. Taniguchi et al have experimentally reported the implementation of AI solid-state nanopores with ML assistance and checked their sensing performance with ionic current–time data of nanoparticles . To tailor a suitable regressor model for the nanopore device, we have checked the prediction capability of all four optimized XGBR models, XGBR_dAMP , XGBR_dTMP , XGBR_dGMP , and XGBR_dCMP .…”
mentioning
confidence: 99%